A critical evaluation of AC pollution flashover models for HV insulators having hydrophilic surfaces - Holtzhausen, Jacobus Petrus (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1997.